Probiotic Lactobacillus rhamnosus GG (LGG) restrains the angiogenic potential of colorectal carcinoma cells by activating a proresolving program via formyl peptide receptor 1. Issue 16 (20th July 2022) - Liotti, Federica; Marotta, Maria; Sorriento, Daniela; Pagliuca, Chiara; Caturano, Valeria; Mantova, Giuseppe; Scaglione, Elena; Salvatore, Paola; Melillo, Rosa Marina; Prevete, Nella
Abstract : Formyl peptide receptors (FPR1, FPR2 and FPR3) are innate immune sensors of pathogen and commensal bacteria and have a role in colonic mucosa homeostasis. We identified FPR1 as a tumour suppressor in gastric cancer cells due to its ability to sustain an inflammation resolution response with antiangiogenic potential. Here, we investigate whether FPR1 exerts similar functions in colorectal carcinoma (CRC) cells. Since it has been shown that the commensal bacterium Lactobacillus rhamnosus GG (LGG) can promote intestinal epithelial homeostasis through FPR1, we explored the possibility that it could induce proresolving and antiangiogenic effects in CRC cells. We demonstrated that pharmacologic inhibition or genetic deletion of FPR1 in CRC cells caused a reduction of proresolving mediators and a consequent upregulation of angiogenic factors. The activation of FPR1 mediates opposite effects. Proresolving, antiangiogenic and homeostatic functions were also observed upon treatment of CRC cells with supernatant of LGG culture, but not of other lactic acid or nonprobiotic bacteria (i.e. Bifidobacterium bifidum or Escherichia coli ). These activities of LGG are dependent on FPR1 expression and on the subsequent MAPK signalling activation. Thus, the innate immune receptor FPR1 could be a regulator of the balance between microbiota, inflammation and cancer in CRC models. Abstract : The commensal probiotic bacteria Lactobacillus rhamnosus GG (LGG), by activating the innate immune receptor formyl peptide receptor 1 (FPR1), influence normal intestinal epithelial homeostasis and sustain wound restitution. We demonstrated that LGG, but not other lactic acid or nonprobiotic bacteria, activate an inflammation resolution program that dampens the angiogenic response of colorectal carcinoma cells.